2022
DOI: 10.3389/fnut.2022.882175
|View full text |Cite
|
Sign up to set email alerts
|

Tilapia Skin Peptides Ameliorate Cyclophosphamide-Induced Anxiety- and Depression-Like Behavior via Improving Oxidative Stress, Neuroinflammation, Neuron Apoptosis, and Neurogenesis in Mice

Abstract: Anxiety- and depression-like behavior following chemotherapy treatment occurs in cancer patients with high probability and no specific therapeutics are available for treatment and prevention of this complication. Here, tilapia skin peptides (TSP), a novel enzymatically hydrolyzed bioactive peptide mixture, obtained from tilapia (Oreochromis mossambicus) scraps, were studied on cyclophosphamide (CP)-induced anxiety- and depression-like behavior in mice. Mice were received intraperitoneal injection of CP for 2 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Studies were consistent in measuring cyclic AMP responsive element binding protein (CREB) activity, in that increased phospho-CREB or CREB levels were associated with an antidepressant response [ 38 , 46 , 81 , 83 , 103 , 109 , 112 ]; remarkably, studies on peripheral tissues in man [ 38 ] and hippocampal content in mice [ 81 ] pointed to the same direction. Additionally, studies of BDNF showed that increased BDNF activity was associated with antidepressant effects and that animals displaying depressive features have low BDNF contents in the periphery and the brain [ 44 , 52 , 57 , 57 , 58 , 66 , 67 , 69 , 81 , 83 , 85 , 88 , 93 , 111 , 112 , 114 , 121 ]. It has recently been shown that most, if not all, antidepressant drugs bring about their antidepressant effects by binding the tyrosine kinase receptor 2 (TrkB), a molecule tied to the action of BDNF [ 127 , 128 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies were consistent in measuring cyclic AMP responsive element binding protein (CREB) activity, in that increased phospho-CREB or CREB levels were associated with an antidepressant response [ 38 , 46 , 81 , 83 , 103 , 109 , 112 ]; remarkably, studies on peripheral tissues in man [ 38 ] and hippocampal content in mice [ 81 ] pointed to the same direction. Additionally, studies of BDNF showed that increased BDNF activity was associated with antidepressant effects and that animals displaying depressive features have low BDNF contents in the periphery and the brain [ 44 , 52 , 57 , 57 , 58 , 66 , 67 , 69 , 81 , 83 , 85 , 88 , 93 , 111 , 112 , 114 , 121 ]. It has recently been shown that most, if not all, antidepressant drugs bring about their antidepressant effects by binding the tyrosine kinase receptor 2 (TrkB), a molecule tied to the action of BDNF [ 127 , 128 ].…”
Section: Discussionmentioning
confidence: 99%
“…Images were photographed under a fluorescence confocal microscope. The experimental method referred to the previous studies with appropriately modified [ 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…A significant number of MNPs are produced by the complex living environment of marine animals, and a novel entity structure and enormous diversity are provided by the chemical structure with strong biological activity ( Zhao et al, 2022a ). Some MNPs have participated in antidepressant preclinical or clinical trials and have proven to be great sources for novel and effective antidepressants ( Tables 1 , 2 ).…”
Section: Subsections Relevant To the Subjectmentioning
confidence: 99%
“…Some MNPs have participated in antidepressant preclinical or clinical trials and have proven to be great sources for novel and effective antidepressants ( Tables 1 , 2 ). The marine environment is a rich source of novel pharmaceuticals, many of the substances found there can regulate brain activity, reduce anxiety, and have potential therapeutic applications for disorders associated with anxiety and depression ( Zhao et al, 2022a ). At present, with the interaction between academia and the pharmaceutical sector, a large number of MNPs have been discovered and tested using current analytical methods.…”
Section: Subsections Relevant To the Subjectmentioning
confidence: 99%